Global entrainment effect on biped robot locomotion energy - Za'balawi, I.I.; Kiong, L.C.; Kiong, W.E.; Senanayake, S.M.N.A. (ACTA Press, 2009)
In recent years, many researchers have studied the generation of rhythmic movement emerge as a stable limit cycle from global entrainment between biological neural networks that include central pattern generators (CPGs) and physical systems (i.e. robot arm) interacting with external environment. However, the eï¬ect of global entrainment on biped locomotion energy has yet to be addressed. This paper delineates an approach to minimize bipedâs locomotion energy by means of global entrainment. The rhythmic movements for biped locomotion such as walking and running are generated by CPG using coupled nonlinear oscillators of Van Der Pol (VDP). Tuning VDP oscillator parameters to meet certain criteria (i.e. minimum energy) is a diï¬cult task to accomplish. This is due to the nonlinearity and the coupling of the oscillators. To overcome these diï¬culties, response surface methodology (RSM) has been proposed to characterize VDP parameters to achieve eï¬cient energy for biped locomotion. Then, global entrainment has been implemented between ï¬ve-link biped robot and the constructed CPG. As a result, the sensory information modulates VDP oscillatorsâ frequencies and tuned them to the resonance frequencies of the biped link lengths. The obtained results show an evidence of the importance of global entrainment in achieving lower energy for biped locomotion while maintaining the same or even higher forward velocity.